Technical investigation on small water leakage incident occurrence in mercury target of J-PARC. Issue 2 (1st February 2018) - Haga, Katsuhiro; Kogawa, Hiroyuki; Wakui, Takashi; Naoe, Takashi; Takada, Hiroshi
ABSTRACT: Japan Proton Accelerator Research Complex experienced failures of two mercury targets, which were Target #5 and #7, in 2015 when the facility was operating with a proton beam power of 500 kW. The failures involved coolant water leak from the water shroud. In this paper, we investigate the root cause of the Target #5 failure. The results of the visual inspections, mockup tests, and analytical evaluations suggested that the water leak was caused by the possible combination of two incidents. One was the diffusion bonding failure due to the large thermal stress induced by welding of the bolt head during the fabrication process, and the other was the thermal fatigue failure of the seal weld due to the repetitive beam shutdown during beam operation. Though the investigation into the root cause of the Target #7 failure is still going on, these target failures point to the importance of eliminating initial defects and the need to secure the rigidity and stability of welded structures. The next mercury target, Target #8, was fabricated with an improved design and fabrication process to reduce the possibility of similar failures. The beam operation of this mercury target is planned to be started in October 2017.